Verificação da ocorrência do efeito índice no IBOVESPA, 2003-2012 - Nardy, Andre (2014)
The dynamics of abnormal returns , volume and betas is analyzed for Bovespa s stocks included or excluded from the Ibovespa index between 2003 and 2012, in a phenomenon known in the financial literature as the index effect, one of the oldest reported anomalies. Event studies are used with different settings of estimation window to measure abnormal returns and assess its effect on the calculation of return for the market model , since the calculation of the theoretical portfolio of Bovespa is known beforehand and is based on marketability and liquidity. No abnormal return is veryfied for shares on the date of their effective entry on the index, only abnormally high volumes. On the date of the first preview of inclusions positive abnormal returns and volumes are observed, and so on for excluded stocks. However, when we exclude from the sample companies with IPOs up to 3 years of its entry into the Bovespa Index and those assets included during the crisis of the financial markets, it appears tha abnormal returns do occur on the effective date, consistent with previous literature on the theme. The betas of the stocks included tend to covariate with greater force after inclusion in the index . With the results achieved market efficiency in the semi-strong form cannot be challenged for the Brazilian stock market, but there is a possible change in the occurrence of the index effect for the period studied, compared with previous studies